(untitled) (Comprehensive Journal of Science, 2025)
This analytical study aimed to understand the impact of growth mindset-focused feedback on learners’ academic self-concept. The study reviewed research literature on the subject, focusing on studies published between 2015 and 2025. The study adopted a thematic analysis methodology, analyzing 27 studies extracted from various scientific databases. The findings revealed that growth mindset-focused feedback generally enhances learners’ academic self-concept through multiple mechanisms, such as promoting a growth mindset. The study also indicated that feedback effectiveness is influenced by factors like gender, educational stage, and cultural context. The study recommends that teachers adopt customized feedback strategies that consider individual differences and support students’ holistic development.